Palmitic Acid Reduces the Autophagic Flux and Insulin Sensitivity Through the Activation of the Free Fatty Acid Receptor 1 (FFAR1) in the Hypothalamic Neuronal Cell Line N43/5 - Hernández-Cáceres, María Paz; Toledo-Valenzuela, Lilian; Díaz-Castro, Francisco; Ávalos, Yenniffer; Burgos, Paulina; Narro, Carla; Peña-Oyarzun, Daniel; Espinoza-Caicedo, Jasson; Cifuentes-Araneda, Flavia; Navarro-Aguad, Fernanda; Riquelme, Cecilia; Troncoso, Rodrigo; et al. (Frontiers in Endocrinology, 2019)
Chronic consumption of high fat diets (HFDs), rich in saturated fatty acids like palmitic acid (PA), is associated with the development of obesity and obesity-related metabolic diseases such as type II diabetes mellitus (T2DM). Previous studies indicate that PA accumulates in the hypothalamus following consumption of HFDs; in addition, HFDs consumption inhibits autophagy and reduces insulin sensitivity. Whether malfunction of autophagy specifically in hypothalamic neurons decreases insulin sensitivity remains unknown. PA does activate the Free Fatty Acid Receptor 1 (FFAR1), also known as G protein-coupled receptor 40 (GPR40); however, whether FFAR1 mediates the effects of PA on hypothalamic autophagy and insulin sensitivity has not been shown. Here, we demonstrate that exposure to PA inhibits the autophagic flux and reduces insulin sensitivity in a cellular model of hypothalamic neurons (N43/5 cells). Furthermore, we show that inhibition of autophagy and the autophagic flux reduces insulin sensitivity in hypothalamic neuronal cells. Interestingly, the inhibition of the autophagic flux, and the reduction in insulin sensitivity are prevented by pharmacological inhibition of FFAR1. Our findings show that dysregulation of autophagy reduces insulin sensitivity in hypothalamic neuronal cells. In addition, our data suggest FFAR1 mediates the ability of PA to inhibit autophagic flux and reduce insulin sensitivity in hypothalamic neuronal cells. These results reveal a novel cellular mechanism linking PA-rich diets to decreased insulin sensitivity in the hypothalamus and suggest that hypothalamic autophagy might represent a target for future T2DM therapies.